From the experience of final qualifying works preparation in secondary technical schools - Artemyeva J. I., Prokopyev A. V. (Educational environment today: development strategy, 2016)
the purpose of this article is to summarize and demonstrate the knowledge gained during working in college based on the experience of research activity of pre-diploma practice and practical training, showing readiness of the young specialists to solve production problems of practical and research character and transfer of teamwork skills in the preparation of the qualified workers.
Keywords: практико-ориентированный подход; выпускная квалификационная работа; интегрированные ВКР; practice-oriented approach; graduation qualification work; the integrated GQW